2004
DOI: 10.1256/qj.02.109
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of data into an ocean model with systematic errors near the equator

Abstract: SUMMARYAssimilation of thermal data into an ocean model near the equator often results in a dynamically unbalanced state with unrealistic deep overturning circulations. The way in which these circulations arise from errors in the model or its forcing and the equatorial dynamics is discussed. A scheme is proposed to calculate a state with a better balance by using the observational increments to the model to update slowly evolving bias fields. These bias fields augment the model state and affect the model's pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 22 publications
2
102
1
Order By: Relevance
“…For this reason, many works point out that the model biases should be considered during the assimilation process Dee and Silva, 1998;Bell et al, 2004;Dee, 2005;Xie and Zhu, 2010). Also, improving the co-variances of the ensemble members may lead to more accurate analyses (Oke et al, 2008;Xie and Zhu, 2010).…”
Section: Adjustment Of the Altimetry And Velocity Fieldsmentioning
confidence: 99%
“…For this reason, many works point out that the model biases should be considered during the assimilation process Dee and Silva, 1998;Bell et al, 2004;Dee, 2005;Xie and Zhu, 2010). Also, improving the co-variances of the ensemble members may lead to more accurate analyses (Oke et al, 2008;Xie and Zhu, 2010).…”
Section: Adjustment Of the Altimetry And Velocity Fieldsmentioning
confidence: 99%
“…This fact limits the use of the proposed method for seasonal numerical experiments. To prevent the reduction of inter-annual variability it is also of interest to try more sofisticated correction methods such as (Bell et al, 2004).…”
Section: Comparison Of Model Results With Observationsmentioning
confidence: 99%
“…Dee and da Silva (1998) have applied this idea to numerical weather prediction. Bell et al (2004) built on the ideas of the latter work and applied a term of "pressure correction" combining it with the augmenting state vector concept.…”
Section: Developed a Continuous Variationalmentioning
confidence: 99%
“…Troccoli et al (2002) reported that the univariate assimilation of temperature profiles, without attempting to correct salinity, can induce spurious convection and result in errors in the subsurface temperature and salinity fields. Bell et al (2004) found that assimilation of temperature data into an ocean model near the equator often results in a dynamically unbalanced state with unrealistically strong vertical motions that corrupt the increments introduced by the data assimilation scheme and lead to an ocean state with a biased density field. To address these problems recent developments have focused on dynamically balanced multivariate analysis schemes for ocean data assimilation.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Troccoli et al (2002) proposed a method to preserve water mass characteristics, and Burgers et al (2002) suggested imposing geostrophically balanced increments to horizontal velocities and density. In addition, various bias estimation and treatment techniques, inspired by Dee and Da Silva (1998), have been proposed for ocean data assimilation (Bell et al 2004;Chepurin et al 2005;Balmaseda et al 2007). However, most of these techniques are not truly multivariate, since the analysis is performed by taking dynamical constraints that are applied a posteriori to a statistically generated univariate analysis.…”
Section: Introductionmentioning
confidence: 99%